Etiological structure of mycobacterial infections of animals in the Dnipropetrovsk region - Tkatschenko, A. A.; Tkatschenko, O. A.; Tkatschenko, Оleksii; Tkachenko, Olexiy; Tkachenko, A. A.; Tkachenko, Oleksiy; Tkachenko, O.; Ткаченко, Олексій Андрійович; Masjuk, D.; Masiuk, Dmytro; Masiuk, D. N.; Masiuk, D. M.; et al. (Published by Primedia eLaunch, 2021)
When carrying out the identification of 14 cultures of mycobacteria, their belonging to four species was established – Mycobacterium bovis, Mycobacterium rhlei, Mycobacterium xenopi, and Mycobacterium vacca. According to the histological investigations, it was found that in the spleen tissue there are drainage foci and sites of caseous necrosis with granulomatous reaction around. The granulomas had the specific character and the characteristic structure for the tuberculous process. The caseous lymphadenitis was noted in lymph nodes. The tissue of the lungs was with reduced airiness at the expense of the expansion of fibrous and granulation tissue with the presence of foci of caseous necrosis, which are surrounded by a layer of epithelial cells, macrophages with admixture of lymphocytes and plasmatic cells. Among the epithelioid cells were gigantic multinucleated cells of the Pirogov-Langhans type. При проведенні ідентифікації 14 культур мікобактерій встановлено їх належність до чотирьох видів (Mycobacterium bovis Mycobacterium рhlei, Mycobacterium xenopi, Mycobacterium vacca). За гістологічного дослідження біоматеріалу від морських свинок встановлено, що у тканині селезінки наявні зливні вогнища і ділянки казеозного некрозу з гранульоматозною реакцією навколо. Гранульоми мали специфічний характер і характерну для туберкульозного процесу будову. У лімфатичних вузлах відмічено казеозний лімфаденіт. Тканина легень була зі зниженою повітряністю за рахунок розростань фіброзної та грануляційної тканини з наявністю вогнищ казеозного некрозу, які оточені шаром епітеліоїдних клітин, макрофагів з домішками лімфоцитів та плазматичних клітин. Серед епітеліоїдних клітин були гігантські багатоядерні клітини Пірогова-Лангханса.
Етіологічна структура мікобактеріальних інфекцій тварин у Дніпропетровській області
Ткаченко Олексій Андрійович http://orcid.org/0000-0003-0978-6575 Масюк Дмитро Миколайович https://orcid.org/0000-0002-2800-2580 Глебенюк Володимир Володимирович https://orcid.org/0000-0001-5599-651X Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X Василенко Тетяна Олександрівна https://orcid.org/0000-0003-3430-868X
Keywords: Mycobacterium bovis; Mycobacterium bovis; tuberculosis; туберкульоз; Dnipropetrovsk region; Дніпропетровська область; pathoanatomical changes; патологоанатомічні зміни; microbiological investigations; мікробіологічне дослідження